Sedem desetletij metasekvoje (Metasequoia glyptostroboides Hu et Cheng) v Sloveniji - Petek, Iza (Acta silvae et ligni, 2024)
The dawn redwood (Metasequoia glyptostroboides Hu et Cheng) is among the most recently discovered tree species on Earth. It is also a very ancient species that has undergone minimal morphological change over millions of years. The species was identified in the middle of the 20th century in China, a mere few years after scientists had discovered its fossilised remains and presumed it to be extinct. Following its discovery, it became the subject of considerable discussion, written analysis and planting initiatives worldwide, driven by the desire to study the species. The discovery of living specimens was a significant event for the botanical community. In the context of climate change and the search for new strategies to enhance forest resilience, the dawn redwood has recently gained renewed attention as a potentially valuable species. The tree’s heavily gnarled trunk and persistence of dead branches can present challenges in processing its highly fungus-resistant wood. However, its distinctive appearance also makes it an aesthetically appealing choice, particularly in urban settings. It is utilised as a commercial species in certain regions of China, but in Europe it is predominantly planted in test plantations and in urban environments. Following seven decades of its presence in Slovenia, this review paper provides a detailed account of its discovery, current utilisation and future potential.
Keywords: drevesne vrste; lastnosti; Metasequoia glyptostroboides; odkritje; Slovenija; zgodovina